PENGARUH PENGAWASAN, KEPUASAN KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN (Studi Empiris pada KL EXPRESS Tidar Malang Periode 2018) - Nishfi Aini Zahra; Hadi Sunaryo; M. Khoirul ABS (UNIVERSITAS ISLAM MALANG, 2018)
ABSTRACT The purpose of this study is to describe the supervision, job satisfaction, work environment, and employee performance and to know the effect of supervision, job satisfaction, work environment on the performance of employees partially or simultaneously. This research method using quantitative method. This research type is explanatory research. The sample of this research is employees of KL Express Tidar Malang by using saturated sampling, that is 35 respondents. Methods of data collection using questionnaires. The method of analysis used in this study is multiple regression analysis with SPSS 14.0 for windows. The results of this study indicate that: (1) There is a positive and significant influence of Supervision on Employee Performance KL Express Tidar Malang. (2) There is influence of Working Tack on employees of KL Express Tidar Malang. (3) There is positive influence and significant Working Environment to Employee Performance KL Express Tidar Malang. Keywords: Supervision, Job Satisfaction, Work Environment and Employee Performance.